Photo-accelerated "click" reaction between diarylsydnones and ring-strained alkynes for bioorthogonal ligation. Issue 50 (5th June 2019) - Zhang, Xiaocui; Wu, Xueting; Jiang, Shichao; Gao, Jingshuo; Yao, Zhuojun; Deng, Jiajie; Zhang, Linmeng; Yu, Zhipeng
Abstract : A novel photo-click ligation reaction between diarylsydnones and ring-strained alkynes, exhibiting decent bioorthogonality, was established under 405 nm light irradiation. Abstract : We constructed a library of diarylsydnone (DASyd) candidates in search of a photoclickable reaction toward alkynes, enabling an ultra-accelerated reactivity, while suppressing the background cycloaddition in the dark. The in vitro and in vivo protein labelling experiments revealed that the photo-accelerated DASyd–alkyne cycloaddition exhibits robust selectivity.